2012
DOI: 10.1002/jcp.22848
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of substance P induces cancer cell death and decreases the steady state of EGFR and Her2

Abstract: NK1 is a tachykinin receptor highly relevant to tumorigenesis and metastasis development in breast cancer and other carcinomas. Despite the substantial efforts done to develop potent NK1 receptor antagonists, none of these antagonists had shown good antitumor activity in clinical trials. Now, we have tested the effect of inhibition of the neuropeptide Substance P (SP), a NK1 ligand, as a potential therapeutic approach in cancer. We found that the inhibition of SP with antibodies strongly inhibit cell growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 39 publications
12
61
0
Order By: Relevance
“…This inhibition of both p70S6K and 4E-BP1/2 produced by manipulation at the NK1R is in accordance with Mayordomo and colleagues (20). However, their group treated breast, prostate, and colon cancer cells and used SP antibodies, thereby targeting NK1R's natural substrate, not the receptor itself.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This inhibition of both p70S6K and 4E-BP1/2 produced by manipulation at the NK1R is in accordance with Mayordomo and colleagues (20). However, their group treated breast, prostate, and colon cancer cells and used SP antibodies, thereby targeting NK1R's natural substrate, not the receptor itself.…”
Section: Discussionsupporting
confidence: 86%
“…The inhibitory effect of aprepitant in other cancer cells such as breast cancer cells was shown to be transmitted at least partially through ERK1/2 (20,21). However, Western blot analysis for ERK1/2 remained virtually unchanged and did not reveal uniform changes, respectively, at the protein level in the three HB cell lines investigated (Fig.…”
Section: Nk1r Antagonism Leads To Differential Expression Of the Akt mentioning
confidence: 89%
“…In particular, previous work showed that the inhibition of hepatoblastoma cell growth could be achieved with the use of rapamycin through inhibition of the PI3K/AKT/mTOR pathway by dephosphorylating and deactivating p70S6K (109). Furthermore, the inhibition of both p70S6K and 4EBP1, in our study, is in accordance with Mayordomo et al (103). This group treated breast, prostate and colon cancer cells with SP antibodies, which led to the inhibition of mTOR.…”
Section: Downstream Mechanisms Following Inhibition Of Hepatoblastomasupporting
confidence: 92%
“…The fact that cancer cells produce SP also suggests the presence of an autocrine growth stimulus pattern. Mayordomo et al used a monoclonal, specific antibody against this agonist in isolated cultures of breast cancer and other cancer cell lines and observed an inhibition of cell growth and an increase of apoptosis (103). Similarly, when using anti-SP or anti-NK1R antibodies, a significant growth inhibition was noted in our study.…”
Section: Therapeutic Innovations In Hepatoblastoma the Nk1r As A Tumosupporting
confidence: 85%
“…Aprepitant, a non-peptide NK1R antagonist, is a clinical agent approved by the Food and Drug Administration for the treatment of chemotherapy-induced nausea and vomiting. Its effects as an anticancer agent have been described extensively in vitro and in vivo (6)(7)(8)(9)(10)(11). Notably, evidence indicates that it has limited toxic side effects even when administered in high doses (6,12).…”
Section: Introductionmentioning
confidence: 99%